FACTOR ANALYSIS OF THE UNDERUTILIZATION OF ISLAMIC PENSION FUNDS IN INDONESIA - M. Luthfi Al Abshor; Haris Nur Ihsan; M. Rizqi Virgiawan Pradana; Rinda Asytuti (JASIE, 2024)
Pension funds are one of the funding system options used to collect funds. It is the means needed to ensure that participants' income remains when they grow old. Law Number 11 of 1992 provides the foundation for pensions in Indonesia, involving Financial Institution Pension Funds (DPLK) and Occupational Pension Funds (DPPK). The purpose of this research is to find out what are the factors for the lack of use of Islamic pension funds in Indonesia. This research uses a qualitative and deductive approach to analyze the management of Islamic pension funds. The results of this study show that Islamic pension funds face challenges, including a lack of supportive regulations, a lack of public awareness, and limited Islamic investment products. Despite the huge growth potential, Islamic pension funds have yet to reach their peak. The government needs to take special measures, including the creation of supportive legislation, as well as raising the credibility of Islamic pension funds. Through increased transparency, strong governance and public education, Islamic pension funds can play an important role in strengthening Islamic finance in Indonesia. These results provide a deeper understanding of the underutilization of Islamic pension funds in Indonesia.